Held [videorecording (DVD)] - Awbrey, Jill; Awbrey, Jill; Johnson, Bart, 1970-; Kempton, Rez (Magnet, Magnolia Home Entertainment, 2021)
A couple's ailing marriage is put to the test when they rent a house for a secluded romantic vacation and are held captive there as a mysterious Voice gives them commands. They must obey or face terrifying consequences.